Influence of indicators of successful combat for the ball on the performance of matches in the Russian premier football league - Suetin P.S. ,; Zakharova A.V. ,; Naboychenko E.S. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the relationship between teams’ performance in successful martial arts and the results of matches in the Russian Premier Football League (RPL). Methods and structure of the study. Based on the results of 120 matches of the first round of the 2023-2024 RPL season. analyzed statistical indicators for martial arts provided by the official RPL data provider, the Yandex Plus - Vsporte platform. The data was processed using mathematical statistics methods using Microsoft Excel Office 365. Results and conclusions. As a result of the study, it was found that only in 47 matches out of 115 (40.9%) the teams that had an advantage in martial arts won. Moreover, in 68 matches out of 115 (59.1%), teams that had a higher percentage of successful combats reduced the match to a draw (33 matches, 28.7%) or lost it (35 matches, 30.4%). In 5 matches there was equality in the percentage of successful combats (50/50), but none of these matches ended in a draw. The results of the study do not confirm the presence of any relationship between the advantage of teams in successful martial arts in general and the results of matches.